Second Footnote on the Tasaday - Salazar, Zeus A. (The Archive; Vol 3 No 1–2 (1972): Vol. 3 (New Series), Nos. 1–2 (1972), 2024)
Excerpt Two new reports issued almost simultaneously by PANAMIN on the Tas., one (Fernandez and Lynch) more scientific in language than the other (Nance), provide an excellent occasion for further comment on our shifting knowledge of this celebrated Filipino group. The Ateneo anthropologists fail to mention, as in a recent pamphlet (:13), that PANAMIN chief Manda Elizalde “is known to the Tasaday as ‘Momo Dakel Diwata Tasaday’ or bringer of good fortune”,1 whereas PANAMIN photographer-turned-ethnographer Nance writes that the 35-year old Harvard graduate Tao Bung or “big man” among Mindanao Minorities (June 12: 19) is also considered by the troglodytic Tas. as “the man their ancestors had foretold would one day come to them” in order to “just love us and help us” (June 8: 6). However, both reports follow the same outline, beginning with the helicopter penetration of the Tas. forest homeland and ending with the humanist exhortation for change through choice and research by invitation. Both likewise exhibit an unfaltering faith in the B’lit Manobo culture hero named Dafal, whose testimony is of prime importance in the determination of the real Tas. techno-economic condition before their presumed “effective isolation” was finally broken after centuries by the scientific entry of PANAMIN.